Становище Руської православної церкви на Херсонщині у другій половині 1940-х – початку 1950-х років - Татарченко, О. (Краєзнавство, 2016)
У статті розповідається про формування в Радянському Союзі ліберальної політики щодо Російської православної церкви протягом Другої світової війни, а також особливості її реалізації на практиці в херсонському регіоні в повоєнні роки. Аналізуються причини охолодження ліберальної політики СРСР щодо РПЦ та вказуються наслідки цього для православної церкви в Херсонській обл. УРСР. В статье рассказывается о формировании в Советском Союзе либеральной политики относительно Российской православной церкви во время Второй мировой войны, а также особенности её реализации на практике в херсонском регионе в послевоенные годы. Анализируются причины охлаждения либеральной политики СССР относительно РПЦ и указываются последствия для православной церкви в Херсонской области УССР. The relevance of this paper is caused by the fact that in the Soviet period researches of Orthodox church history, based on the principle of an objectivism, couldn't be realized through domination of atheistic ideology in a historiography of the Soviet Union. The researches, devoted to the peculiarities of the Soviet policy implementation concerning the Orthodox Church in the post-war period in the Kherson region, aren't created in the Ukrainian historiography to the present days. The reasons for the formation of the Soviet state liberal policies cocerning the Russian Orthodox Church during the World War II, and especially its implementation in practice in the Kherson region are analyzed in this paper. It is told about the ways the local orthodox communities used the new religious legislation of the USSR for receiving in use of cult constructions, what demands were made to them and what duties were assigned. The attention is drawn to the personnel support of parishes, to the policy of the Soviet power concerning the Orthodox clergy. Information about the church buildings which were withdrawn by the power from the Orthodox church, their number and ways of the expropriated objects use is presented. The reasons of the USSR liberal policy cooldowning are concerned in the paper. The consequences of such actions on the example of the Kherson region are specified.